2022
DOI: 10.1021/acsenergylett.1c02522
|View full text |Cite
|
Sign up to set email alerts
|

Continuum Model to Define the Chemistry and Mass Transfer in a Bicarbonate Electrolyzer

Abstract: Bicarbonate electrolyzers are devices designed to convert CO 2 captured from point sources or the atmosphere into chemicals and fuels without needing to first isolate pure CO 2 gas. We report here an experimentally validated model that quantifies the reaction chemistry and mass transfer processes within the catalyst layer and cation exchange membrane layer of a bicarbonate electrolyzer. Our results demonstrate that two distinct chemical microenvironments are key to forming CO at high rates: an acidic membrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 69 publications
(127 reference statements)
1
62
0
Order By: Relevance
“…1a). [22][23][24][25][26][27][28][29][30][31][32][33][34] The industrial-standard CO 2 capturing medium is a 30 wt% mono-ethanolamine (MEA) aqueous solution that has a high CO 2 absorption capacity and kinetics. 31 However, inferior selectivity toward CO or formate has been exhibited in the amine-based capturing solvent compared with that of the conventional CO 2fed electrochemical reduction reaction (CO 2 RR).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1a). [22][23][24][25][26][27][28][29][30][31][32][33][34] The industrial-standard CO 2 capturing medium is a 30 wt% mono-ethanolamine (MEA) aqueous solution that has a high CO 2 absorption capacity and kinetics. 31 However, inferior selectivity toward CO or formate has been exhibited in the amine-based capturing solvent compared with that of the conventional CO 2fed electrochemical reduction reaction (CO 2 RR).…”
Section: Introductionmentioning
confidence: 99%
“…34,35 Because of the low activity of the cCO 2 RR in amine-based solvents, (bi)carbonate-based electrolytes containing relatively small alkali metal cations have mostly been studied for the cCO 2 RR. [22][23][24][25][26][27][28][29][30] However, amine-based solvents are widely developed for the CO 2 capturing process and CO 2 absorption in (bi)carbonate solutions is much more sluggish compared to that in amine-based solvents. 36 Moreover, CO 2 absorption and regeneration rates are controllable depending on the various structures of the amine molecules and thermal-swing and the combination of amine-based molecules can be optimized for the application.…”
Section: Introductionmentioning
confidence: 99%
“…Protons could also cause an acidic local reaction environment close to the catalyst surface and contribute to the unwanted hydrogen evolution reaction. 67,68 Our recent two-phase one-dimensional model for direct bicarbonate reduction unveiled that the rate of CO evolution can be limited more by the formation and mass transfer of CO 2 . Under high current densities, protons tend to either directly get reduced to hydrogen or react with the hydroxyls produced, so CO 2 regeneration and reduction pathways are limited 68 .…”
Section: Free Dissolved Co 2 As the Active Reactantmentioning
confidence: 99%
“…68 Employment of proton-conducting membrane 45 or bipolar membrane 75 could ensure the proton supply to the solvents. Modelling studies 67,68 have shown that by adjusting the thickness, porosity and permeability of the catalyst layer, together with the thickness and ion transport activity of the cation membrane or bipolar membrane, bicarbonate electrolysers can reach higher activity and selectivity under lower cell voltages.…”
Section: Cell Configurationmentioning
confidence: 99%
“…A lower CO 2 RR selectivity at low current densities (<50 mA cm −2 ) is a known phenomenon in CO 2 -RR [26][27][28] and might be connected to a low local pH at the cathode catalyst. 15,29,30 At high current densities FE CO drops to 75% at 150 mA cm −2 and 60% at 200 mA cm −2 .…”
Section: Catalysis Science and Technology Papermentioning
confidence: 99%